PENGARUH JARAK TANAM DAN PEMBERIAN PUPUK ORGANIK CAIR DI GROW TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG DAYAK (Eleutherine americana Merr) - T. Rosmawaty; Zulkifli; Mardani (DINAMIKA PERTANIAN, 2019)
Dayak onion has many benefits, namely anti-inflammatory, stopping the bleeding, anti-breast cancer, heart disease prevention, immunostimulant, anti-tumor, high blood pressure-lowering drugs (hypertension), and diabetes. Dayak onion bulbs contain flavonoids, saponins, polyphenols, alkaloids, glycosides, steroids, phenolics, tannins, triterpenoids, and quinones. DI Grow liquid organic fertilizer is the latest generation of organic fertilizer in agriculture. This fertilizer contains nutrients at a balanced level and also plant growth regulators such as auxin, gibberellin, and cytokinin. This research aims to find out the interaction and the main effect of planting distance and DI Grow liquid organic fertilizer to the growth and the yield of Dayak onion. The research was carried out in the Experimental farm of the Faculty of Agriculture, Islamic University of Riau, Pekanbaru. This research was carried out during 7 months, starting from April to November 2018. The experimental design is a Completely Randomized Factorial Design. The observed parameters are the relative growth rate, net assimilation rate, the number of clump tubers, clump wet weight, and clump dry weight. The results showed that the interaction between planting distance and DI Grow fertilizer did not significantly affect on all the observed parameters. The main effect of planting distance and DI Grow fertilizer was found on all parameters with the best treatment at a planting distance of 25x30 (J4) and DI Grow fertilizer dose of 9 ml/L of water (D3).